Historical trends of the age in artistic gymnastic across World Championships and the Olympic Games from 1896 to 2016 - a cross-sectional data analysis - Atikovic, A. (International Scientific Congress Slovenian Gymnastics Federation, 2017)
The OG and WC represent the crown of each athlete`s career, so it is the same with gymnasts. That is why you can safely assert that the best competitors come to these competitions. Up until 1981 the minimum age for participating in senior competitions was 14 years of age. At the 58th FIG Congress held in July 1980, a short time before the OG in Moscow, the minimuWWpart in the competition as seniors. These age requirements have not changed until 1997 when the minimum age rose from 15 to 16 years of age (Anderson, 1997).Since 1997 the gymnasts had to be at least 16 years old or to be turning 16 within the calendar year in order to take part in the competition as seniors. At the 2016 OG, the gymnast had to be born before 01/01/2001. The oldest female gymnast currently competing in senior international events is Uzbekistan's Oksana Chusovitina, 41 (b. 1975) old at the (seven) OG. She was 17 years, 1 month old at her first Olympics, the 1992 Summer Olympics. Bulgaria's Yordan Yovchev, 39 (b. 1973), who became the first ever male gymnast to compete in (six) OG. There is no maximum age restriction, and some gymnasts compete well into their 30's.